Analysis of SIPD Acceptance at Bappeda Bulungan Regency Using the Technology Acceptance Model Method - Juani, Elisabet; Harahap, Dian Pransisko; Saelan, Athia (IKRA-ITH Informatika : Jurnal Komputer dan Informatika, 2026)
Digital transformation in local government governance requires effective use of information systems, particularly in regional development planning, control, and evaluation. One of the nationally implemented systems is the Regional Government Information System (SIPD). This study aims to analyze user acceptance and actual usage of SIPD among employees of the PPEPD Division at the Regional Development Planning Agency (Bappeda) of Bulungan Regency using the Technology Acceptance Model (TAM). This research employed a descriptive quantitative method with a survey approach involving 51 active SIPD users. Data were collected through a five-point Likert scale questionnaire measuring Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Attitude Toward Using (ATU), Behavioral Intention to Use (BITU), and Actual System Use (ASU). The results indicate that all TAM variables fall into good to very good categories, with an overall mean score of 4.14. PU achieved the highest score (4.20), indicating that SIPD is perceived as highly beneficial, while PEOU recorded the lowest score (4.09), although still categorized as good. These findings suggest that SIPD has been well accepted and practically implemented, yet improvements in system usability are still required.